Prediksi Laju Erosi dan Valuasi Ekonomi pada Area Reklamasi Pertambangan Batu Bara - Arief Adi Pradana; Dwi Nowo Martono; Soemarno Witoro Soelarno (Universitas Negeri Jakarta, 2021)
Mining activities had positive and negative impacts on the environment. Erosion is one of the negative impacts that must be managed. This research carried out due to the problem of different predicted erosion and the actual condition in one of the reclamation areas of PT X. This research aims to analyze the erosion rate and economic value on the mining reclamation activities of PT X. This research method carried out using the calculation of erosion rates with USLE, the Erosion Hazard Index (IBE), interviews with village communities around PT X and calculated economic value due to erosion with an economic valuation using Total Economic Value (NET). The results indicate that the calculation of erosion rates with the USLE approach of 35,351.69 tons/ha/year and the value of the Erosion Hazard Index (IBE) with the Very High category dominating reclamation area with a percentage of 61,11%. The results of the economic valuation calculation are Rp13,7 billion/year, and the recommended erosion management is to manage factors C and P to reduce the rate of erosion.